Cytogenetic identification and molecular marker development of a novel wheat-Leymus mollis 4Ns(4D) alien disomic substitution line with resistance to stripe rust and Fusarium head blight - Du, Xin; Feng, Xianbo; Li, Ruoxuan; Jin, Yanlong; Shang, Lihui; Zhao, Jixin; Wang, Changyou; Li, Tingdong; Chen, Chunhuan; Tian, Zengrong; Deng, Pingchuan; Ji, Wanquan (Frontiers in Plant Science, 2022)
Leymus mollis (Trin.) Pilg. (2n = 4x = 28, NsNsXmXm) potentially harbours useful genes that might contribute to the improvement of wheat. We describe M862 as a novel wheat-L. mollis alien disomic substitution line from a cross between wheat cv. 7182 and octoploid Tritileymus M47. Cytological observations indicate that M862 has a chromosome constitution of 2n = 42 = 21II. Two 4D chromosomes of wheat substituted by two L. mollis Ns chromosomes were observed, using the GISH and ND-FISH analyses. Molecular marker, 55K SNP array and wheat-P. huashanica liquid array (GenoBaits®WheatplusPh) analyses further indicate that the alien chromosomes are L. mollis 4Ns. Therefore, it was deduced that M862 was a wheat-L. mollis 4Ns(4D) alien disomic substitution line. There were also changes in chromosomes 1A, 1D, 2B and 5A detected by ND-FISH analysis. Transcriptome sequencing showed that the structural variation of 1D, 1A and 5A may have smaller impact on gene expression than that for 2B. In addition, a total of 16 markers derived from Lm#4Ns were developed from transcriptome sequences, and these proved to be highly effective for tracking the introduced chromosome. M862 showed reduced height, larger grains (weight and width), and was highly resistance to CYR32 and CYR34 stripe rust races at the seedling stage and mixed stripe rust races (CYR32, CYR33 and CYR34) at the adult stage. It was also resistance to Fusarium head blight (FHB). This alien disomic substitution line M862 may be exploited as an important genetic material in the domestication of stipe rust and FHB resistance wheat varieties.